Kinetic-Catalytic-Spectrophotometric Determination of Trace Amounts of Tellurium(IV) by its Catalytic Effect on the Reduction of Brilliant Cresyl Blue with Sodium Sulfide in Cationic Micellar Medium - KEYVANFARD, M.; A. ENSAFI, ALI (Asian Journal of Chemistry, 2010)
A simple and sensitive kinetic-spectrophotometric method is proposed for the determination of ultra trace amounts of tellurium(IV). It is based on the catalytic effect of Te(IV) on the reduction of brilliant cresyl blue by sodium sulfide in presence of cetyl trimethylammonium bromide as a micellar media. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of brilliant cresyl blue at 635 run for 0.5-2.0 min from initiation of the reaction. Calibration curve is linear over the concentration range of 0.004-0.200 and 0.20-1.00 μg/mL of Te(IV) with a detection limit of 0.6 ng/mL. The relative standard deviation for ten replicates determination of 0.040 and 0.100 μg/mL Te(IV) was 0.8 and 1.2%, respectively. The method was applied for the determination of tellurium in synthetic samples.